Polysaccharide extraction from Myxopyrum smilacifolium trunk and its antioxidant capacity - Hieu, Le Trung; Le Lam, Son; Nguyen Dang Giang, Chau; Nguyen Minh, Nhung; Tran Thanh, Minh; Ho Xuan Anh, Vu; Le Thuy, Trang; Nguyen Viet, Thang; Nguyen Quang, Man; Tran Thi Van, Thi (Hue University Journal of Science: Natural Science, 2023)
As a traditional medicinal plant in Vietnam, Myxopyrum smilacifolium has been used for a long history to treat cough, nervous disorders, numbness, rheumatism, and cephalalgia. Nevertheless, reports on the antioxidant activity and extraction of M. smilacifolium polysaccharides are still very rare. This study was designed to extract a high yield of polysaccharides from the M. smilacifolium trunk and characterize it. As a result, the maximum yield of the polysaccharides of 5.13 ± 0.05% was obtained with an extraction time of three hours, extraction temperature of 100 oC, the ratio of water to sample of 1:50 as extraction solution, extraction number of times 3, and the ratio of ethanol to extract volume 5:1 (v/v). Polysaccharides was characterized by Fourier transform infrared spectroscopy (FT-IR) and high-performance gel-permeation chromatography (HPGPC). The average molecular weight of extracted polysaccharides was around 3.78 × 105 Da. In vitro assays dan impressive antioxidant activities of the extracted polysaccharides, containing 0.2423 ± 0.0028 mg GA/g or 0.2142 ± 0.0007 μmol AS/g. The IC50 values of polysaccharides in the DPPH and ABTS methods were 0.89 mg/mL and 3.85 mg/mL, respectively. These findings exhibited the potential for application or further research and development of polysaccharides from Myxopyrum smilacifolium.